2022
DOI: 10.33988/auvfd.795247
|View full text |Cite
|
Sign up to set email alerts
|

Marker-assisted introgression of myostatin from Texel to Ramlıç sheep: Growth and real-time ultrasound carcass traits in F1 and BC1 lambs

Abstract: The aim of the study was to evaluate live weights, body measurements, and real-time ultrasound carcass traits of F1 and BC1 genotypes in a marker assisted introgression (MAI) process. Effects of some factors on live weight and body measurements including ultrasonographic assessments in Musculus longissimus dorsi (MLD) were investigated at the F1 (n=51) and BC1 (n=99) cross lambs born in 2015 -2017 period. Variance analysis showed that genotype had significant (P < 0.001) effect on pre-and post-weaning growth c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
3
8
0
Order By: Relevance
“…In contrast, Moghani pure lambs were significantly ( P < 0.05) heavier at birth compared to F2 crossbred lambs with the Booroola mutation in the homozygous variant genotype (G/G). This aligns with the findings of Çelikeloglu et al [ 19 ] and Tekerli et al [ 20 ], who conducted studies on the introgression of the MSTN mutation into Turkish Ramlıç sheep. Their findings indicated that Texel sheep with the MSTN mutation in homozygous form (A/A) exhibited significantly lower body weights in comparison to Ramlıç sheep with the wild-type genotype (G/G), as well as to the first-generation backcrosses (BC1, G/G and G/A) and the second-generation backcrosses (BC2, G/G and G/A) lambs [ 19 , 20 ].…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…In contrast, Moghani pure lambs were significantly ( P < 0.05) heavier at birth compared to F2 crossbred lambs with the Booroola mutation in the homozygous variant genotype (G/G). This aligns with the findings of Çelikeloglu et al [ 19 ] and Tekerli et al [ 20 ], who conducted studies on the introgression of the MSTN mutation into Turkish Ramlıç sheep. Their findings indicated that Texel sheep with the MSTN mutation in homozygous form (A/A) exhibited significantly lower body weights in comparison to Ramlıç sheep with the wild-type genotype (G/G), as well as to the first-generation backcrosses (BC1, G/G and G/A) and the second-generation backcrosses (BC2, G/G and G/A) lambs [ 19 , 20 ].…”
Section: Resultssupporting
confidence: 91%
“…This aligns with the findings of Çelikeloglu et al [ 19 ] and Tekerli et al [ 20 ], who conducted studies on the introgression of the MSTN mutation into Turkish Ramlıç sheep. Their findings indicated that Texel sheep with the MSTN mutation in homozygous form (A/A) exhibited significantly lower body weights in comparison to Ramlıç sheep with the wild-type genotype (G/G), as well as to the first-generation backcrosses (BC1, G/G and G/A) and the second-generation backcrosses (BC2, G/G and G/A) lambs [ 19 , 20 ]. Moreover, the A allele of the MSTN mutation OAR2:g.118150665G>A exerted a non-significant adverse impact on live weight traits in Texel sheep [ 49 ], Norwegian White sheep [ 50 ], Turkish Ramlıç sheep [ 19 ], and New Zealand Romney sheep [ 51 ].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Based on reference SNP ID assigned by dbSNP rs408469734, it is located on OAR2, position 118 150 665 of the genome assembly Oar_v3.1 (Figure 4). Recent studies revealed successful experiences in improving carcass traits after introgression of MSTN g + 6223G>A from Texel into the Ramlıç Turkish sheep (Çelikeloglu et al, 2022; Tekerli et al, 2022).…”
Section: Major Genes Related To Muscle‐related Traits In Sheepmentioning
confidence: 99%